Roseovarius amoyensis sp. nov. and Muricauda amoyensis sp. nov., isolated from the Xiamen coast. Issue 10 (22nd July 2019) - Li, Guizhen; Lai, Qiliang; Yan, Peisheng; Shao, Zongze
Abstract : Strain GCL-8 T and GCL-11 T were isolated from Guanyinshan, a sandy beach on the Xiamen coast. Cells of the two strains were Gram-stain-negative, catalase-positive, oxidase-positive, rod-shaped and non-motile. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strains GCL-8 T and GCL-11 T belonged to the genera Roseovarius and Muricauda, with the highest sequence similarities to Roseovarius indicus B108 T (96.5%) and Muricauda antarctica CGMCC 1.12174 T (97.3%), respectively. The major fatty acids of strain GCL-8 T were summed feature 8 (C18:1 ω7 c /ω6 c ), C19:0 cyclo ω8 c, C16:0 and C17:0, while the major fatty acids of strain GCL-11 T were iso-C15:1 G, iso-C15:0 and iso-C17:0 3-OH. The G+C contents of the chromosomal DNA of strains GCL-8 T and GCL-11 T were 64.1 mol% and 45.67 mol%, respectively. The respiratory quinones of strains GCL-8 T and GCL-11 T were Q-10 and MK-6, respectively. The polar lipids of strain GCL-8 T were diphosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, one unidentified aminophospholipid, one unidentified aminolipid, three unidentified phospholipids and three unidentified polar lipids. The polar lipids of strain GCL-11 T were phosphatidylethanolamine, seven unidentified phospholipids and four unidentified polar lipids. The combined genotypic and phenotypic data show that strains GCL-8 T and GCL-11 T represent two novel species within genera Roseovarius and Muricauda, for which the names Roseovariu samoyensis sp. nov. and Muricauda amoyensis sp. nov. are proposed, with type strains GCL-8 T (=MCCC 1A11651 T = KCTC 52430 T ) and GCL-11 T (=MCCC 1A11649 T =KCTC 52432 T ).